2015
DOI: 10.1007/s00246-015-1182-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hypertension During Pregnancy and the Risk of Congenital Heart Defects in Offspring: A Systematic Review and Meta-analysis

Abstract: Maternal hypertension is common during pregnancy, and multiple studies have reported on an association between maternal hypertension and congenital heart defects (CHDs) in offspring; however, there is variability in the quality of these studies. A systematic review and meta-analysis was conducted on the associations between untreated and treated maternal hypertension and the risk of CHDs, evaluating CHDs overall as well as specific CHD subtypes. A systematic search of peer-reviewed articles published before Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 37 publications
2
76
2
3
Order By: Relevance
“…25 Some studies have discussed an increased risk for cardiac defects in treated and untreated pregnancies with hypertension. [26][27][28][29][30] The small number of major birth defects in our study does not allow further analysis with regard to other organ systems like urogenital malformations that were previously reported to be associated with antihypertensive treatment. 31 However, there is no distinct pattern of congenital anomalies among exposed neonates, neither in our prospective cohort nor among our retrospective reports.…”
Section: Birth Defectsmentioning
confidence: 74%
“…25 Some studies have discussed an increased risk for cardiac defects in treated and untreated pregnancies with hypertension. [26][27][28][29][30] The small number of major birth defects in our study does not allow further analysis with regard to other organ systems like urogenital malformations that were previously reported to be associated with antihypertensive treatment. 31 However, there is no distinct pattern of congenital anomalies among exposed neonates, neither in our prospective cohort nor among our retrospective reports.…”
Section: Birth Defectsmentioning
confidence: 74%
“…This association may therefore reflect a physiological effect of lowering the maternal blood pressure rather than a drug-specific teratogenic effect, or may be causally related to the underlying maternal hypertension (Ramakrishnan et al, 2015).…”
Section: Teratogenicitymentioning
confidence: 98%
“…Epidemiological studies have identified significant environmental risk factors for human CHD, including maternal exposures to alcohol, isotretinoin, thalidomide, antiseizure medications, antiretroviral medications, environmental teratogens and infectious agents. Embryo hypoxia is another well-recognized risk factor caused by smoking, living at high altitude, maternal diabetes, high body mass index, hypertension or prescription medications (Watkins et al, 2003;Jenkins et al, 2007;Zheng et al, 2013;Webster et al, 2014;Ornoy et al, 2015;Ramakrishnan et al, 2015;Sullivan et al, 2015). The specific effects of environment on embryonic development have been studied by exposing pregnant animals to a variety of conditions.…”
Section: Introductionmentioning
confidence: 99%